2018
DOI: 10.1111/resp.13271
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinflation of bronchi in vitro impairs bronchodilation to simulated breathing and increases sensitivity to contractile activation

Abstract: Hyperinflated bronchi exhibit reduced bronchodilation to breathing and increased sensitivity to bronchoconstrictor stimuli. Findings suggest that hyperinflation may directly alter airway function by reducing the protective effects of DI and initiating contraction at low doses of contractile stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…Cairncross et al . showed that hyperinflation directly alters the properties of isolated bronchial segments, reducing the protective effects of deep inspiration and making bronchi more sensitive to contractile stimuli . This work sheds light on the complex relationships between lung volume, bronchoconstriction and airway hyperresponsiveness …”
Section: Copdmentioning
confidence: 72%
“…Cairncross et al . showed that hyperinflation directly alters the properties of isolated bronchial segments, reducing the protective effects of deep inspiration and making bronchi more sensitive to contractile stimuli . This work sheds light on the complex relationships between lung volume, bronchoconstriction and airway hyperresponsiveness …”
Section: Copdmentioning
confidence: 72%
“…In this issue of the journal, the study by Cairncross et al . examines yet another issue in the ongoing saga of lung inflation and airway responsiveness, albeit one that has thus far received little attention.…”
mentioning
confidence: 99%
“…Perhaps, more important and peculiar to ASM versus other types of muscle is length adaptation. The bronchial rings investigated by Cairncross et al . were maintained at either 5 or 25 cm H 2 O for 2 h prior to being studied, which is probably long enough for the contractile machinery to adapt towards optimum forced generation at the corresponding ASM lengths, especially as viability studies were performed in the interim that would have facilitated adaptation.…”
mentioning
confidence: 99%
See 2 more Smart Citations